2019
DOI: 10.1371/journal.pmed.1002790
|View full text |Cite
|
Sign up to set email alerts
|

Alternate aerosol and systemic immunisation with a recombinant viral vector for tuberculosis, MVA85A: A phase I randomised controlled trial

Abstract: Background There is an urgent need for an effective tuberculosis (TB) vaccine. Heterologous prime–boost regimens induce potent cellular immunity. MVA85A is a candidate TB vaccine. This phase I clinical trial was designed to evaluate whether alternating aerosol and intradermal vaccination routes would boost cellular immunity to the Mycobacterium tuberculosis antigen 85A (Ag85A). Methods and findings Between December 2013 and January 2016, 36 ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 29 publications
4
29
0
Order By: Relevance
“…Furthermore, it has been shown that intranasal application of MVA expressing a secreted form of the bovine herpesvirus 1 (BoHV-1) glycoprotein D protects against BoHV-1 infection in a rabbit model (19). Application of MVA vector vaccines via the respiratory route has been shown to be safe in general (16) but respiratory adverse effects have been reported after intramuscular priming and inhalative boosting with MVA expressing the 85A antigen of Mycobacterium tuberculosis (20).…”
Section: Mva and Baltmentioning
confidence: 99%
“…Furthermore, it has been shown that intranasal application of MVA expressing a secreted form of the bovine herpesvirus 1 (BoHV-1) glycoprotein D protects against BoHV-1 infection in a rabbit model (19). Application of MVA vector vaccines via the respiratory route has been shown to be safe in general (16) but respiratory adverse effects have been reported after intramuscular priming and inhalative boosting with MVA expressing the 85A antigen of Mycobacterium tuberculosis (20).…”
Section: Mva and Baltmentioning
confidence: 99%
“…It was found that the VACV strains can differ significantly in terms of their pathogenicity and reactogenicity. Furthermore, the route of inoculation with the virus can also significantly affect its pathogenic and immunogenic properties [21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…First phase IIb efficacy trials with this vaccine in neonates and in adults failed to provide protection (102,103). More recently, the vaccine has been tested for safety and immunogenicity after aerosol application (104,105). Other viral vectored vaccines include replication deficient adenovirus vectors expressing antigen Ag85A and a replication deficient H1N1 influenza vector expressing antigen Ag85A and ESAT-6.…”
Section: Immunopathology Of Tuberculosismentioning
confidence: 99%